Relationship Between Midface Volume Deficits and the Appearance of Tear Troughs and Nasolabial Folds. Issue 12 (December 2018) - Glaser, Dee Anna; Lambros, Val; Kolodziejczyk, Julia; Magyar, Andrew; Dorries, Kathleen; Gallagher, Conor J.
Abstract : BACKGROUND: Understanding interrelationships among aging facial features is important in facial aesthetics as a global treatment approach becomes standard. OBJECTIVE: Examine empirical relationships between midface volume deficit and severity of tear troughs (TTs) and nasolabial folds (NLFs) in women and men of different racial/ethnic groups. METHODS: A web-based study was administered to health panel members (aged 18–75 years). Participants compared their midface volume, TTs, and NLFs against photonumeric scales depicting degrees of severity. Linear regressions were conducted to assess the relationship of midface volume on severity of TTs and NLFs, controlling for demographic factors. RESULTS: Of 4, 086 participants (80.0% female), 3, 553 had complete data. Increasing severity of midface volume deficit was associated with increasing severity of TTs and NLFs in both sexes (all p < .001). Race/ethnicity was associated with differences in severity in all 3 facial areas, although specific differences between races/ethnicities varied for women and men. Progression rates of severity differed between racial/ethnic groups. Correlations between midface volume deficit, TTs, and NLFs were positive and significant (all p < .001). CONCLUSION: Midface volume deficit was associated with severity of TT deformity and NLFs after controlling for age and other demographic variables. Abstract : Supplemental Digital Content is Available in the Text.